Effectiveness of Stormwater Best Management Practices in Urban Land Developments - Basnayaka, Amila; Sarukkalige, Priyantha Ranjan; Kannangara, Dumal (IB2E - BALWOIS, 2012)
Australian local governments urge to practice the water sensitive urban designs and best management practices in urban land development processes to protect the pre-development hydrology in the post- development stage. This usually comes with the best management practices guided by the local governments and environmental protection authorities. Under the best management practices, one criterion is retaining runoff from post development 1 year 1 hour Average Recurrent Interval (ARI) event within the development site for runoff quality control by treating the initial runoff as close as to the source. In this study, soakage wells, bio retention swales and rainwater tanks were modeled to cater 1 year ARI runoff within the development. Their impact on reduction of required 5 year and 100 year ARI event runoff storage was studied. One of the Western Australia’s residential development consist of about 118 ha was selected as the case study. The XPSWMM hydrodynamic computer model has been used to do the numerical modeling. It has shown 70% of 5 year runoff volume and 34% 100 of year required storage capacities has been reduced by applying above best management practices. Cost effectiveness of the methods used to cater 1 year ARI event was discussed. The results will be used to develop the urban water management plan for the development site.